Análise do comportamento mecânico do aço inoxidável austenítico AISI 201LN: um modelo experimental para os mecanismos de endurecimento na deformação plástica - Braga, Diogo Pedrino (Universidade Federal de São Carlos, 2024)
The deformation-induced transformation of austenite (γ) into martensite εHCP and α’ (TRIP – Transformation-induced Plasticity) increases the plastic deformation and the hardening in austenitic steels with low stacking fault energy (SFE), providing an increase in simultaneous strength and toughness. The kinetics of this transformation can be affected by variables involved in the plastic deformation process, such as temperature, strain rate and deformation mode. In this work, the general plastic deformation behavior of an austenitic stainless steel (ASS) stabilized with manganese and nitrogen (AISI 20lLN/UNS S20153) was investigated through tensile and compression tests over a wide temperature range (-100° C at 800° C) and strain rate (10-4 to 10-2 s-1); thereafter, at intervals of interest, a more detailed investigation was carried out. Based on the results of mechanical tests and classical models for plastic deformation due to dislocation slip (Voce) and for deformation-induced martensitic transformation (Olson-Cohen) and deformation-induced twinning (Hall-Petch), constitutive equations were proposed seeking to describe the plastic deformation behavior of the material, emphasizing the collaboration of the active mechanisms during each interval. The terms of these equations were parameterized as a function of thermal activation, encompassing the joint effects of temperature and strain rate. A detailed microstructural characterization (X-ray diffraction – XRD and electronbackscattered diffraction - EBSD) was also carried out, correlating the microstructural evolution of the material with the observed plastic deformation behavior. Under the imposed conditions, the 201LN showed a TRIP behavior up to 100° C and between this temperature and 600° C the TWIP mechanism was predominant, with an interval in which these mechanisms overlapped. A significant difference was found between the behavior in tension and in compression, where the proposed model proves to be assertive for predicting the behavior in tension.
Mechanical behavior analysis of the AISI 201LN austenitic stainless steel: an experimental model for hardening mechanisms in plastic deformation
Keywords: Aço Inoxidável austenítico; AISI 201LN; Deformação plástica; Efeito TRIP; Microestrutura; EFE; Austenitic stainless steel; Plastic deformation; TRIP; Microstructure; SFE; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::METALURGIA FISICA